2020
DOI: 10.1016/j.stem.2020.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Multimerization of Zika Virus-NS5 Causes Ciliopathy and Forces Premature Neurogenesis

Abstract: Zika virus (ZikV) is a flavivirus that infects neural tissues, causing congenital microcephaly. ZikV has evolved multiple mechanisms to restrict proliferation and enhance cell death, although the underlying cellular events involved remain unclear.Here we show that the ZikV-NS5 protein interacts with host proteins at the base of the primary cilia in neural progenitor cells, causing an atypical non-genetic ciliopathy and premature neuron delamination. Furthermore, in human microcephalic fetal brain tissue, ZikV-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 78 publications
1
39
0
Order By: Relevance
“…NPCs are critical for brain development as they differentiate into the glial and neuronal cells that compose the majority of the brain parenchyma (Martínez-Cerdeño & Noctor, 2018). Proposed molecular mechanisms by which ZIKV disrupts NPC function and differentiation include perturbation of ANKLE2/VRK1, centrosomal organization, autophagy, apoptosis and unfolded protein response pathways (Link et al, 2019; Ojha et al, 2018; Saade et al, 2020; Shah et al, 2018; Wen et al, 2019). However, it remains unknown how ZIKV manipulates multiple cellular pathways at once to cause such widespread developmental reprogramming.…”
Section: Introductionmentioning
confidence: 99%
“…NPCs are critical for brain development as they differentiate into the glial and neuronal cells that compose the majority of the brain parenchyma (Martínez-Cerdeño & Noctor, 2018). Proposed molecular mechanisms by which ZIKV disrupts NPC function and differentiation include perturbation of ANKLE2/VRK1, centrosomal organization, autophagy, apoptosis and unfolded protein response pathways (Link et al, 2019; Ojha et al, 2018; Saade et al, 2020; Shah et al, 2018; Wen et al, 2019). However, it remains unknown how ZIKV manipulates multiple cellular pathways at once to cause such widespread developmental reprogramming.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that ZIKV is also able to induce premature differentiation of NPCs into mature neurons ( Gabriel et al, 2017 ; Saade et al, 2020 ). Notably, the levels of generated mature neurons did not accumulate and remained at a steady level, indicating that ZIKV is able to trigger differentiation of NPCs and then induce apoptosis of the newly generated neurons ( Gabriel et al, 2017 ).…”
Section: Premature Differentiation Of Neural Progenitor Cellsmentioning
confidence: 99%
“…During asymmetric division, the daughter cell inheriting the mature centriole reforms the primary cilia, thus maintaining attachment to the ventricular surface and the status as an NPC. The other daughter cell will not reform a primary cilium, and will thus undergo delamination, basal migration and maturation into a neuron ( Figure 6 ) ( Gilmore and Walsh, 2013 ; Saade et al, 2020 ). Inheritance of the mature centriole is key to reforming the primary cilium, as it forms the core of the primary cilium basal body structure, and associates with Cep164 centrosomal protein to allow primary cilia assembly ( Graser et al, 2007 ).…”
Section: Premature Differentiation Of Neural Progenitor Cellsmentioning
confidence: 99%
See 2 more Smart Citations